Pharmacokinetic Modelling of Methotrexate from Routine Clinical Data in Patients with Acute Lymphoblastic Leukemia: Methotrexate Pharmacokinetic Modelling - Jebabli, Nadia; Jebari, Hanen El; Gares, Emna; Salouage, Issam; Trabelsi, Sameh; Hamza, Imen; Klouz, Anis; Lakhal, Mohamed (Biological Sciences - PJSIR, 2013)